Community Empowerment Based on Creative Economy in Processing Palm Sap into Palm Sugar Through Home Industry - Faridawati; Edi Jusriadi; Buyung Romadhani (GoodWill, 2025)
This study aims to identify the potential of human resources in an effort to develop and empower the home industry group processing palm sugar into ant sugar based on a creative economy. This type of research is qualitative, with data collection techniques using interviews with 20 informants from elements of the home industry group, village and sub-district governments, the BUMDes as a companion. The data analysis technique used triangulation starting from data reduction, presentation, and drawing conclusions. The results of the study found that: 1) The potential of human resources for the home industry group from the aspect of quantity was adequate, but the quality aspect of education was not adequate with an average education level of elementary school (SD), 2 ) Efforts to develop human resources for the home industry group were carried out through training and mentoring carried out by the Village government and BUMDes, and 3) empowerment of the home industry fostered group for palm sugar processing in Pattalassang District, Gowa Regency, has not been optimal, because there is still a lack of knowledge and life skills in conducting business innovations, home industry groups are more likely to sell in the form of palm wine or palm wine. processed into alcoholic wine because it makes money faster.